Frequency of microsatellite instability in gynecologic cancers and the efficacy of immune checkpoint inhibitors treated: real-world data from a single gynecologic center - Kuang, Wei; Zeng, Jing; Tong, Lingling; Liu, Qianqi; Sun, Huanxin; Feng, Min; Liang, Dongni; Wang, Wei; Wang, Cheng (Frontiers in Immunology, 2025)
ObjectiveThis study evaluated the incidence of Microsatellite Instability-High (MSI-H) in patients with gynecologic cancers in a single gynecologic center and investigated the effect of immune checkpoint inhibitors (ICIs) in treating MSI-H in advanced or recurrent gynecologic cancers.MethodsWe conducted a retrospective study of patients diagnosed with gynecological cancers between June 2021 and May 2024. We investigated their clinicopathological information, the results of microsatellite instability (MSI), the immunohistochemistry staining PD-L1 analyses, the molecular classification testing, and the tumor response to treatment with ICIs.ResultsAmong 1333 patients included in the analysis, the frequency of MSI-H was 1.3% (3/223) in cervical cancer, 25.7% (280/1091) in endometrial cancer, and 10.5% (2/19) in ovarian or tubal and peritoneal cancer. When the patients were evaluated by histologic type, the frequency of MSI-H was 26.1% (241/921) in endometrioid adenocarcinoma and 35.1% (20/57) in mixed adenocarcinoma. Molecular classification results for the 1020 cases that successfully underwent the tests were 71 for the POLE mutation (POLEmut) subtype, 271 for MMR-deficiency (MMRd) subtype, 571 for the non-specific molecular profile (NSMP) subtype, and 107 for the p53 abnormality (p53abn) subtype. Thirty-five patients were treated with ICIs for at least one cycle. The objective response rate (ORR) was 34.3% (95% CI, 19.1% to 52.2%). Among the patients who achieved an objective response, the median time to respond was 2.65 months, and the median duration of response had not been reached. The median progression-free survival (PFS) was 9 months (95% CI, 4 to 10), and the median overall survival (OS) had not been reached. Additionally, in the patients with endometrial cancer, the median PFS in MSI-H patients was 5 months versus 3 months in microsatellite stable (MSS) patients (Δ = 2 months; p=0.92), and the median OS in both MSI-H and MSS patients had not been reached (p=0.89).ConclusionThis study had shown the MSI-H frequencies for the three major types of gynecological tumors and demonstrated the clinical benefit of treatment with ICIs in patients with advanced or recurrent gynecologic cancer. Among endometrial cancer patients, the effects of immunotherapy may be consistent regardless of MSI status.